Báo cáo tiếp thu, giải trình, chỉnh lý Dự án Luật Giá (sửa đổi) (kèm theo báo cáo tóm tắt) - Uỷ ban Thường vụ Quốc hội (2023)
Toàn văn Báo cáo tiếp thu, giải trình, chỉnh lý Dự án Luật Giá (sửa đổi) (kèm theo báo cáo tóm tắt).